Co-inoculation of rhizobium strains and one of the arbuscular micorrhizal fungus on Stylosanthes guianensis cv. CIAT-184 - Crespo Flores, Gustavo; Ramírez, J. F.; González, P. J.; Hernández, I. (Cuban Journal of Agricultural Science, 2016)
The effect of the co-inoculation of three rhizobium strains and one of the arbuscular micorrhizal fungus (AMF) on Stylosanthes guianensis cv. CIAT-184 was evaluated. The experiment was carried out in the Pastures and Forages Station of Cascajal, Villa Clara province, in a ferruginous nodular Gley soil. Eight treatments were studied: the rhizobium strains S1, S2 and S3 alone and combined with the AMF species Funneliformes mosseae, a control with F. mosseae without rhizobium and another without rhizobium or F. mosseae. Treatments were distributed in a random block design with four replications. Results of the first two cuttings are presented. S2 and S3 strains increased significantly the nodulation (31-40 nodules/plant) and the nitrogen concentration in the aerial biomass (3.55-4.00 %) regarding S1 and the control treatments. F. mosseae increased percentages of frequency and colonization intensity and the spore density in the rhizosphere, as well as the P concentrations in the aerial biomass (0.25 %). The co-inoculation of both microorganisms improved the effectiveness of the nodulation and increased the micorrhizal structures and Stylosanthes yield. Best results were obtained with S2 and S3 strains in presence of F. mosseae. It was confirmed under the conditions of this study the synergic effect of the nitrofixing bacteria and the arbuscular micorrhizal fungi, as well as the advantages of the co-inoculation of both microorganisms for improving yield and nutritive value of Stylosanthes, at least during its establishment. Key words: biological nitrogen fixation, arbuscular micorrhiza, forage legumes, nutrition